Development of Android Applications to Disseminate Media about Patient Safety Goals for Nurses - Buhari, Basok; Sutrisno, Deny (KnE Life Sciences, 2021)
Patient safety is an essential part of nursing services and an indicator of the quality of hospital services. One strategy helping to improve the quality of service provided by health workers (especially nurses) is learning about patient safety goals. One form of learning media used is an android application on a mobile smartphone. This application is based on the assessment of material experts, media experts, and nurses. This study uses a development method adapted from the 4D model which consists of four stages, namely: 1) define; (2) design; (3) develop; and (4) disseminate. The results shows the feasibility of creating effective and efficient patient safety goals teaching materials as an interactive learning multimedia for android mobiles. The result indicate: 1) material experts with an percentage of 83.7% which falls into category of very decent; 2) media experts with an percentage of 80% which falls into category of decent; 3) Nurses as a user with an percentage of 86.6% which falls into the very good category. Therefore, it can be concluded that the an android application to disseminate this learning material would be useful and feasible for nurses. Keywords: patient safety, android application, nurses, mobile smartphone